Epistemologi Sufi dalam Penafsiran Huruf Muqaṭṭa‘āt: : Analisis Tafsir Isyārĭ dalam Ḥaqā’iq al-Tafsĭr Karya al-Sulamĭ - Afiyah, Nur; Ali, Asyiq Billah; Mahabbatus Shalihah , Alicia (Universitas Islam Negeri Madura, 2025)
Sufi exegesis of the isyārĭ type continues to be a subject of debate, as it is often regarded as subjective, weak in terms of verifiable transmission, and potentially prone to departing from the literal (ẓāhir) meaning of the Qur’an. This article responds to these concerns by examining how Abū ‘Abd al-Raḥmān al-Sulamĭ (d. 412 H/1021 M) constructed an epistemic foundation for mystical interpretation in his work Ḥaqā’iq al-Tafsĭr, focusing specifically on the case of the muqaṭṭa’āt (disjointed letters). This study employs a qualitative library-based approach, using Ḥaqā’iq al-Tafsĭr and al-Sulamĭ’s works related to the malāmatiyyah tradition as primary sources, supported by scholarship on the historical development of Sufism in Khurāsān and the discourse on the science of letters. The analysis is conducted through qualitative content analysis and historical-contextual interpretation using an operational A-B-C coding scheme. The findings demonstrate that al-Sulamĭ’s reading of the muqaṭṭa’āt is not merely a form of individual symbolism, but rather a structured epistemic practice articulated through a stratification of meaning between ẓāhir and isyārah, spiritual authorization mediated through networks of early Sufi authority, and an ethical-spiritual validation oriented toward transformative experience. This article highlights the contribution of this interpretive model while also acknowledging its limitations, particularly the requirement of coherence with the ẓāhir meaning and adherence to the discipline of spiritual propriety (adab).